Molecular analysis of Biofilm genes in Micrococcus luteus Isolated from Pleural Fluid Infections Patients in Al-Najaf Province, Iraq - Hala Ridha Abbas Al-Fahham1; Zahraa Yosif Motaweq (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Micrococcus luteus is a low-virulence opportunistic pathogen that has been identified as an emerging hospital pathogen. Infections caused by M. luteus have increased over the years due to increased high-risk patients e.g. patients with immune suppression, hematological malignancies, ICU admission. Therefore this study conducted to characterization and investigation of some virulence factor particularly detection of biofilm formation in order to determinants the role of this bacteria in causing infection in Al-Najaf province. Therefore 250 clinical specimens were collected from plural fluid infection 140 (64.9%) of specimens were collected from male and 110 (35.1%) from female, the specimens were cultured on suitable media and cultivated at 37℃. The results showed that 209 (76.9%) gave bacterial growth while 41 (23.1%) appeared no growth. After identification of bacterial isolate, 25 of isolates were identified M. luteus recovered from the pleural fluid infections. TCP method were used to determinant the predominant of the level of biofilm among M. luteus isolates, the results of TCP revealed that all isolate 25 (100%) were biofilm formation. The results of genetic analysis of pml gene revealed that 7 (28%) of M. luteus isolates have this gene.